How to: molecular investigation of a hospital outbreak. (June 2019) - Nutman, A.; Marchaim, D.
Abstract: Background: Studying hospital outbreaks by using molecular tools, i.e. synthesizing the molecular epidemiology data to its appropriate clinical-epidemiologic context, is crucial in order to identify infection source, infer transmission dynamics, appropriately allocate prevention resources and implement control measures. Whole-genome sequencing (WGS) of pathogens has become the reference standard, as it is becoming more accessible and affordable. Consequently, sequencing of the full pathogen genome via WGS and major progress in fit-for-purpose genomic data analysis tools and interpretation is revolutionizing the field of outbreak investigations in hospitals. Metagenomics is an additional evolving field that might become commonly used in the future for outbreak investigations. Nevertheless, practitioners are frequently limited in terms of WGS or metagenomics, especially for local outbreak analyses, as a result of costs or logistical considerations, reduced or lack of locally available resources and/or expertise. As a result, traditional approaches, including pulsed-field gel electrophoresis, repetitive-element palindromic PCR and multilocus sequence typing, along with other typing methods, are still widely used. Aims: To provide practitioners with evidenced-based action plans for usage of the various typing techniques in order to investigate the molecular epidemiology of nosocomial outbreaks, of clinically significant pathogens in acute-care hospitals. Sources: PubMed search with relevant keywords along with personal collection of relevant publications. Content: Representative case scenarios and critical review of the relevant scientific literature. Implications: The review provides practical action plans to manage molecular epidemiologic investigations of outbreaks caused by clinically significant nosocomial pathogens, while prioritizing the use and timely integration of the various methodologies.